Assessing Turkish Preservice English Teachers’ 21st Century Skills - Ghorbandordinejad, Farhad; Almarfi, Amal Mohamed Abdulsalam (JETLi: Journal of English Teaching and Linguistics, 2023)
In recent years, there has been a growing recognition of the importance of 21st century skills in preparing individuals for success in the modern workforce. These skills, which include critical thinking, creativity, collaboration, communication, and digital literacy, are seen essential for individuals to navigate the complex and rapid change of global landscape. For language teachers, in particular, these skills are crucial in helping students develop the language proficiency and cultural competence necessary to communicate effectively in today's interconnected world. However, despite the recognized importance of these skills, there is limited literature on how to assess them among pre-service language teachers. To address this gap, a study was conducted to evaluate the level of 21st century skills among pre-service English language teachers in Turkish universities. The study sought to determine if there was a significant difference in the mean scores on the five latent variables of 21st century skills between two groups of pre-service teachers: group 1 consisting of freshmen and sophomores (45 students), and group 2 comprising juniors and seniors (41 students). The study utilized a survey questionnaire as the data-gathering tool and conducted a multivariate analysis of variance to analyze the data. The results of the analysis revealed a Wilks' Lambda value of .978 and a significance value of 0.674, indicating that there was no statistically significant difference between the two groups regarding their 21st century skills. Despite this lack of difference, the study highlights the importance of exposing pre-service language teachers to 21st century skills and monitoring their learning, literacy, and life skills. The study recommends that Turkish universities' pre-service language teacher education programs should incorporate these skills into their curriculum to ensure that their graduates are well-equipped to meet the demands of the modern workforce and contribute to a more globally connected and culturally competent society.